ANALISIS GHARAR PADA ENDORSMENT - Fitra, Audina (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
Gharar, in the context of Islamic law, refers to unwanted uncertainty or unclear risks in a transaction. In endorsements, the gharar factor may arise due to uncertainty regarding how the use of the celebrity will affect the perception and sales of the product.